110k views
4 votes
PLZ HELP! Solve the system of equations using the substitution method

y=-3x+7

x=-2y-16

x=__

y=__

User Mohgeroth
by
5.1k points

1 Answer

3 votes

Answer:

x=6,y=-11

Explanation:

y=-3x+7

x=-2y-16

Substitute the second equation into the first every place you see an x

y=-3(-2y-16)+7

Distribute

y = 6y+48 +7

Combine like terms

y = 6y +55

Minus 6y from each side

y-6y = 6y-6y+55

-5y = 55

Divide by -5

-5y/-5 = 55/-5

y = -11

Now we need to find x

x=-2y-16

x = -2(-11) -16

x =22-16

x = 6

x=6, y= -11

User Sherif
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.